Awapuhi – a pine cone ginger extract / Siti Nurul Atikah Abu Samah and Nor Azma Yusuf - Abu Samah, Siti Nurul Atikah; Yusuf, Nor Azma (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
Zingiber zerumbet (L.) Smith or locally known as “lempoyang” and pine cone ginger in Malaysia has been extensively studied particularly in pharmacological field because of its tremendous medicinal benefits. However, little knowledge is available on the cultivation science which lead to varying rhizome yield depending on practices. The maintenance practice of pine cone ginger is rather expensive to produce high quality raw material. Therefore, based on the preliminary study, the optimum fertilizer formulation which significantly increased the yield with high quality of phytochemical properties is NPK 60:70:0. The objective of this invention idea is to formulate a nutraceutical product namely “Awapuhi – A Pine Cone Ginger Extract”. This invention idea is developed with low cost production but high yield extract potential. This invention will help small scale growers to increase their raw material (rhizome yield) production in the form of the biomass and phytochemical quality. On the other hand, the small-scale business owners who are in the nutraceutical and functional food industries will get benefit by selling high value products based on the pine cone ginger extracts. This product invention is expected to increase the amount of raw materials in the market aligned with the current National Agrofood Policy 2021-2030 where herbal plants have been listed as one of the High Value Commodities (HVC). Therefore, this invention idea will help to tremendously increase the market supply by using the recommended fertilization requirements specifically for pine cone ginger.